2010
DOI: 10.1002/hed.21312
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal treatment of patients with minor salivary gland cancer in the case of recurrent disease

Abstract: The initial tumor classification is a clinical predictor for patients' overall and disease-free survival and overall survival after recurrence. Multimodal treatment significantly improves patients' overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 21 publications
0
14
0
4
Order By: Relevance
“…Recently, Erovic et al . found that the T stage at presentation was a predictor of patients' disease‐free survival, but N stage was not 46 . Further, we suggest that prognostic factors related to NAC should be analyzed.…”
Section: Staging Systemmentioning
confidence: 69%
See 1 more Smart Citation
“…Recently, Erovic et al . found that the T stage at presentation was a predictor of patients' disease‐free survival, but N stage was not 46 . Further, we suggest that prognostic factors related to NAC should be analyzed.…”
Section: Staging Systemmentioning
confidence: 69%
“…In a study at SYSUCC by Guo et al ., 17 the local control rate and the 5‐year disease‐free survival rate were 79 and 75% ( P = 0.724) in the radiotherapy‐treated group ( n = 32), and 90 and 89% ( P = 0.724) in the surgery plus radiotherapy ( n = 10) group, respectively. Early‐stage disease (T1 or T2) has been shown to be equally well controlled with either radiotherapy or surgery alone, but for advanced‐stage (T3 or T4) disease, combination radiotherapy following by surgery may significantly improve locoregional control rates 46,48–50 . ACC has a higher locoregional control rate (LRCR) than other histological types.…”
Section: Treatment and Prognosismentioning
confidence: 99%
“…There are only a few reports of EGFR blockade to treat patients with recurrent MEC [6]. However, response was not observed for cetuximab monotherapy [16].…”
Section: Schlüsselwörtermentioning
confidence: 99%
“…The endoscopic endonasal technique permits a safe and feasible removal in selected cases, with promising oncologic outcomes and lower morbidity than with the external approaches . Moreover, adjuvant treatments can be associated to improve survival and reduce the risk of recurrences …”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, adjuvant treatments can be associated to improve survival and reduce the risk of recurrences. 10 The aim of this study was to analyze the clinical features, surgical treatment, and the survival outcomes in patients affected by ACC and treated endoscopically.…”
Section: Introductionmentioning
confidence: 99%